Women's modal switching behavior since driving is allowed in Saudi Arabia. (October 2021) - Al-Garawi, Najah; Kamargianni, Maria
Abstract: The objective of this paper is to explore if and how the primary transport mode of women in Saudi Arabia changed since they are allowed to issue a driving license and drive, and what the factors affecting modal switch behavior are. A survey was launched as part of the national project She Drives KSA a year after the activation of the decree on allowing women drive. 20, 504 women participated in the survey. Data analysis shows that modal shifts happened to several directions. A significant percentage of women (22.7%) has switched from "household car-as a passenger" to "household car-as a driver". In total, 37.7% of the participants have switched to household car-as a driver. A nested logit model is developed and the model estimation results indicate that employed women, women in the age groups of 18 to 29 and 30 to 39, women with high educational level, and single women are more likely to change from "household private car-as a passenger", "ridehailing" and "other" to "household private car-as a driver". Women who are unemployed, with low educational level and from households with low monthly income, are more likely to not change their primary transport mode. To our knowledge, this is the first research investigating such a unique and sensitive topic that is expected to significantly affect women's travel behavior. Highlights: The paper explores if and how the primary transport mode of women in Saudi Arabia changed since they are allowed to drive. It is the first research investigating such a unique and sensitive topic that is expected to affect travel behavior. 20, 504 women participated in the survey. 37.7% of the participants have switched to household car-as a driver. The model indicates that employed women, are more likely to change "household private car-as a driver". Unemployed women, with low educational level are more likely to not change their primary transport mode.